Eksplorasi Praktik Pariwisata Regeneratif Dalam Pemulihan Dan Pengelolaan Lingkungan Di Desa Kembang Kuning - Samsudin; Amrullah; M. Marzuki (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2026)
The paradigm shift in global tourism from mass tourism towards sustainable tourism, and now evolving into regenerative tourism, is driven by increasing environmental degradation and the limitations of sustainable approaches that only maintain conditions without restoring the damage already done. The urgency of this study lies in the importance of applying a transformative regenerative tourism approach that focuses on active ecosystem restoration, particularly on a community scale at the tourism village level which has limited environmental capacity, such as in Kembang Kuning Village, East Lombok Regency. This study aims to examine in depth regenerative tourism practices in environmental restoration and to assess the involvement of local communities as key actors in environmental management, to answer what constitutes concrete implementation and participation of the local community in the area. Using an exploratory qualitative research design, data were collected through observation techniques, in-depth interviews with key informants, and documentation, which were then analyzed using thematic analysis methods. The main findings of the study show that regenerative tourism in Kembang Kuning Village is realized through integrated environmental management, such as organic waste separation and the strengthening of collaborative governance based on mutual cooperation and local wisdom. These findings provide an important theoretical contribution to the literature on community-based regenerative tourism in Indonesia by proving that active community participation is able to shift tourism orientation towards long-term ecosystem restoration. In conclusion, regenerative tourism is effectively implemented at the rural level when supported by inclusive collaborative governance, with implications for the need for local government regulations and tourist awareness in conservation. Future research is recommended to conduct quantitative studies on the macro-economic impact and to develop specific metrics for measuring the success of regenerative tourism in other nature-based destinations.